Exploring the Association Between Electronic Wearable Device Use and Levels of Physical Activity Among Individuals With Depression and Anxiety: A Population Level Study - Onyeaka, Henry; Firth, Joe; Enemuo, Valentine; Muoghalu, Chioma; Naslund, John; Baiden, Philip; Torous, John (Frontiers in Digital Health, 2021)
ABSTRACT Aim The aim of the present study was to investigate the cross-sectional association between self-reported use of electronic wearable devices (EWD) and levels of physical activity among a representative sample of adults with depression and anxiety in the United States. Methods For this cross-sectional study, data was pooled from the Health Information National Trends Survey 2019. A sample of 1,139 adults with self-reported depression and anxiety (60.9% females; mean age of 52.5 years) was analyzed. Levels of physical activity and prevalence of EWD utilization were self-reported. Chi-square tests was used to compare individual characteristics by EWD use. Multivariable logistic regression was employed to investigate the association between EWD and physical activity levels while adjusting for sociodemographic and health-related factors. Results Of the 1,139 adults with self-reported depression and anxiety, 261 (weighted percentage 28.1%) endorsed using EWD in the past year. After adjusting for covariates, use of EWD use was only significantly associated with a higher odds of reporting intention to lose weight (OR 2.12; 95% CI 1.04, 4.35; p = 0.04). We found no association between EWD use and meeting the national weekly recommendation for physical activity or resistance/strength exercise training. Conclusion About three in ten US adults with depression and anxiety reported using EWD in the past year. Our findings indicate that among people living with mental illness, EWD use is associated with a higher odds of weight loss intent suggesting that EWD may serve as an opening for clinical interactions around physical health through identifying patients primed for behaviour change. Further large-scale studies using randomized trial designs are needed to examine the causal relationships between EWD and physical activity in people with mental health conditions.